A survival analysis approach to determine factors associated with non-retention of newly hired health workers in Iran - Vahid Ghavami; Seyed Saeed Tabatabaee (BMC, 2023)
Abstract Background and aim One of the main tasks of the healthcare human resource management is to maintain and retain professional staff. The high level turnover of professional staff may reduce the quality of healthcare service delivery. Therefore, this study investigated the factors associated with the turnover of the newly recruited healthcare professionals using survival analysis method in Iran. Materials and methods This historical cohort analysis comprised 6811 employees who began working at Mashhad University of Medical Sciences between 2005 and 2020. Employees recruited at any of the university's units between the years 2005 to 2019 were included. We used appropriate descriptive indices and Log-rank test and the Cox proportional-hazards model to assess the staff turnover. A significance level of 0.05 was used for all tests. Results The findings of the survival analysis showed that the probability of turnover in one year, two years, and five years of employment were 0.12, 0.16, and 0.27. Based on the findings of the Log-rank test, the probability of turnover in entire of the study period was not statistically different between male and female (p = 0.573), and likewise between employees with healthcare occupations and non-healthcare occupations (p = 0.351). Employees whose current workplace and birthplace were not similar had a significantly higher probability of turnover (p < 0.001). Accordingly, the Cox regression result showed, the risk of turnover for the singles was 1.22 times higher than the married. For the Ph.D degree was 3.23 times higher compared to those with a diploma or an associate degree, and for a bachelor's or master's degree was 2.06 times more likely to change their workplace than those with a diploma or an associate degree. Conclusion Policies promoting the recruitment of native-born professionals, given priority to the married candidates than single ones, and/or recurring candidates to pledge to stay in the locality of recruitment site can increase the staff retention and reduce the costs of staff turnover including re-hiring, initial and on-the-job training, accommodation, and other extra living consumptions away from home and family.